Identification of Secondary Metabolite compounds and Testing of Flavonoid Levels in Beluntas Leaves (Pluchea indica L.) - Salamah, Forrela Zahwa; Ramadhani, Mieta Widya; Wahidah, Shinta Nuriyah; Rahmawati, Rizka Dwi; Sjakoer, Nour Athiroh Abdoes; Savana, Amartya Gesit; Ramadhan, Majida; Faisal, Faisal; Nafisa, Nafisa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Most Indonesian people still use traditional medicine because Indonesian medicinal plants can potentially be the main ingredient in medicine They contain various types of natural chemical compounds with diverse pharmacological and biodiversity effects. Several plants that usually grow around the yard and are easy to grow are beluntas (Pluchea indica (L.)). Beluntas are consumed as an additional ingredient when eating or processed as a herbal concoction. This study identified secondary metabolite compounds and total flavonoid levels in beluntas leaves. Beluntas leaves (Pluchea indica (L.)) were extracted using ethanol solvents and then tested using several reagents to identify their compound content. The total flavonoid test in the beluntas leaf extract was also conducted by adding a 10% aluminum chloride solution, sodium acetate, and aquadest to the extract sample, then incubated and measured for absorption using UV-Vis spectrophotometry in the wavelength range between 415-440 nm. This study demonstrates that beluntas leaves contain bioactive compounds including steroids, alkaloids, flavonoids, and tannins with a total flavonoid content recorded at 71.567±70.446 mg/g.